2013
DOI: 10.7314/apjcp.2013.14.2.673
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Gastric Cancer Incidence in Tehran by Two-Source Capture-recapture

Abstract: Introduction: Capture-recapture methods have been suggested for reducing costs of disease registration as well as reducing bias in incidence estimations. This study aimed to estimate the gastric cancer incidence in theTehran metropolis population during 2002-2006. Materials and Methods: We investigated new cases of gastric cancer reported by three sources; death certificates, pathology reports, and medical records to Tehran population-based cancer registry during 2002-2006. G 2 statistics and the two-source ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
1
15
1
Order By: Relevance
“…In addition, our results suggested that sex ratio was 1.53 which is more than study performed in Tabriz province (Bafandeh et al, 2006). Stomach, in the present study, the mean age of patients was about 65 years old which was less than Chinese study (Zhou et al, 2008) and another report from Iran (Aghaei et al, 2013) but similar to some other studies and references (Kumar, 2007;Lauwers, 2009;Babaei et al, 2010;Rampazzo et al, 2012;Rodríguez-Vargas, 2013). In Iran, a study from Khuzestan province (in south of the country) showed a mean age of 60 years (Hajiani et al, 2006) subsequently a study from a referral center in Tehran showed mean age of 56 years (Abdi-Rad et al, 2006).…”
Section: Figure 1 Trend Of Registered Patients Of Esophageal and Gassupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, our results suggested that sex ratio was 1.53 which is more than study performed in Tabriz province (Bafandeh et al, 2006). Stomach, in the present study, the mean age of patients was about 65 years old which was less than Chinese study (Zhou et al, 2008) and another report from Iran (Aghaei et al, 2013) but similar to some other studies and references (Kumar, 2007;Lauwers, 2009;Babaei et al, 2010;Rampazzo et al, 2012;Rodríguez-Vargas, 2013). In Iran, a study from Khuzestan province (in south of the country) showed a mean age of 60 years (Hajiani et al, 2006) subsequently a study from a referral center in Tehran showed mean age of 56 years (Abdi-Rad et al, 2006).…”
Section: Figure 1 Trend Of Registered Patients Of Esophageal and Gassupporting
confidence: 87%
“…Sex ratio in our study was higher than some other studies (Newnham et al, 2003;Hajiani et al, 2006;Mousavi and Somi, 2009;Rampazzo et al, 2012;Aghaei et al, 2013;Rodríguez-Vargas, 2013) and what has been reported in Global Cancer Statistics (Jemal et al, 2011). …”
Section: Figure 1 Trend Of Registered Patients Of Esophageal and Gascontrasting
confidence: 64%
“…The results also show that in all the selected centers, females had higher cancer registrations than males. Regarding this difference, the results of the present study is similar to Bailly's (Bailly DOI:http://dx.doi.org/10.7314/APJCP.2015.16.13.5549 Completeness of Cancer Registration in Shiraz Selected Centers through two Source Capture Re-Capture Method, 2009Data et al, 2011) study in France and McClish's (McClish and Penberthy, 2004 , while it is in contrast with Zemestani's (Zemestani et al, 2013) study, Ghojazadeh's (Ghojazadeh et al, 2013) investigation, Aagahi's (Aghaei et al, 2013) study in Tehran, Croccetti's (Crocetti et al, 2001) study in Tuscany, Italy, and Seddon's (Seddon DJ and Williams EMI., 1997) in England. According to the WHO's (2008) report the patterns of stomach cancer registration are similar in males and females (Boyle and Levin, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This method has been documented earlier (Seddon and Williams., 1997;Crocetti et al, 2001;McClish, Penberthy, 2004;Siva et al, 2009 ;Peragallo et al, 2011;Kroll et al, 2011;Aghaei et al, 2013;Ghojazadeh et al, 2013;Zemestani et al, 2013),. For analyzing and estimating the completeness of cancer registration they mostly used Chapman and Chao by a confidence interval of 95%.…”
Section: The Study Consists Of Five Stepsmentioning
confidence: 99%
“…An estimation of the incidence of all cases compared to registered cases or in other words, completeness level of cancer registration is one of the main parts of quality control in such registration. Incomplete record system faces the incidence and survival values calculation with distortion (Aghaei et al, 2012). This is important enough that frequently an important part of quality control in cancer registration reported by the International Association for Research on Cancer (IARC) is based on the estimated cases number in community-not based on the registered cases (Parkin, 1994;Schouten et al, 1994;Ghojazadeh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%